Can the Delay in Antarctic Polar Vortex Breakup Explain Recent Trends in Surface Westerlies? - Sheshadri, Aditi; Plumb, R.A.; Domeisen, Daniela; id_orcid:0 000-0002-1463-929X (Journal of the Atmospheric Sciences, 2014)
ISSN:0022-4928 ISSN:1520-0469